2021
DOI: 10.1002/ceat.202000501
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation Using Plastic Waste, Paper Waste, and Coal as Fuel in a Chemical Looping Combustion Batch Reactor

Abstract: A comparative study of chemical looping combustion (CLC) with paper, plastic, and coal as fuel was carried out. Experiments were performed in a laboratory fluidized‐bed reactor by alternating between reduction and oxidation cycles. The results obtained indicated that a higher temperature leads to an increase in the CO2 yield and carbon conversion for all fuels. Paper had the highest fractional conversion of CO to CO2 followed by polyvinyl chloride (PVC) and coal. This was due to the higher fraction of volatile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…For instance, experiments with plastic and paper waste have been performed in a batch fluidized bed. 33 The first continuous CLC test with waste pellets has been conducted in a 150 kW unit. 34…”
Section: ■ Clc Of Solid Fuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, experiments with plastic and paper waste have been performed in a batch fluidized bed. 33 The first continuous CLC test with waste pellets has been conducted in a 150 kW unit. 34…”
Section: ■ Clc Of Solid Fuelsmentioning
confidence: 99%
“…Thus far, limited results of CLC operation with waste as fuel have been published. For instance, experiments with plastic and paper waste have been performed in a batch fluidized bed . The first continuous CLC test with waste pellets has been conducted in a 150 kW unit…”
Section: Clc Of Solid Fuelsmentioning
confidence: 99%
“…Resulting from three decades of research, a wealth of knowledge has been created for the chemical looping technology in terms of the oxygen carrier selection and performance, reactor design and operation, and the overall technological feasibility, primarily in the context of CO 2 capture from fossil fuel combustion via chemical looping combustion (CLC). 13–51 Shown in Fig. 2a, CLC technologies generally involves two cyclic steps: (1) the use of metal oxide(s) oxygen carrier as the oxidant to fully combust fossil fuels such as coal or methane; (2) the regeneration of the reduced metal oxide(s) in step 1 with air.…”
Section: Introductionmentioning
confidence: 99%
“…In [10], a process simulation was carried out for a 60MWth CLC plant, fired by SRF, which achieved a very high carbon capture efficiency of 97% and had an oxygen demand of 17%, in order for the flue gas to be fully converted in the post-oxidation chamber. What is more, Yaqub et al, in [11] conducted experiments with plastic and paper waste in a batch fluidizedbed reactor, which showed that the paper waste had a higher fractional conversion of CO to CO2, due to its augmented volatile content. This study analyses the implementation of the CLC technology with waste-derived fuels.…”
Section: Introductionmentioning
confidence: 99%